The status of statelessness 60 years on - Türk, V (Refugee Studies Centre, University of Oxford, 2014)
The 60th anniversary of the 1954 Convention on the Status of Stateless Persons is an opportunity to draw attention to the human face of statelessness, and to increase awareness of the impact of this issue on both the lives of individuals and societies more broadly